Highly Efficient Bifunctional Dielectric Metasurfaces at Visible Wavelength: Beam Focusing and Anomalous Refraction in High-Order Modes - Xu, Zhenyu; Li, Zhiwei; Tian, Yanqing; Wei, Yunbing; Wu, Fei (Frontiers in Physics, 2020)
Metasurface is an artificially arranged sub-wavelength micro-structure array, where each structure can be regarded as a unit cell that is controlled by electromagnetic waves. Recently, bifunctional metasurfaces have garnered increasing interest and become excellent candidates for device miniaturization and integration. In this study, we propose a highly efficient bifunctional metasurface composed of silicon nanopillars, enabling beam anomalous refraction and focusing at visible wavelength. Based on the proposed metasurface, the other two metasurfaces demonstrating high-order beam anomalous refraction and focusing are designed successfully. This work will establish a positive prospect for the development of high-performance bifunctional metasurfaces.